PERAN STRATEGIS TELEVISI KOMUNITAS DALAM PEMBERDAYAAN MASYARAKAT - Hartanto - (Pascasarjana Institut Seni Indonesia Surakarta, 2010)
â€œGrabag TV, one of the few active community television stations in Indonesia. Grabag TV was founded in 2005 by Hartanto, a lecturer from the Jakarta Institute of the Arts and native of Grabag. At the time, Grabag residents could only receive the commercial television channel RCTI, relayed from Jakarta by antenna because of the villageâ€™s mountainous surroundings. Grabag TV has a small studio, provided basic equipment, and organised training sessions on script-writing, filming and editing. Using the existing antenna, villagers began broadcasting programs written and produced by their fellow citizens. Grabag TV, has two-hour broadcasts every Monday, Wednesday and Friday afternoon. Any villager with an idea for a program or a general interest in broadcasting is welcome to make a contribution. Farmers and traders go on air to talk about their professional problems, plans and strategies. Programs have featured students from primary and secondary schools discussing the positive and negative effects of television on education, part of Grabag TVâ€™s efforts to raise the media literacy of Grabagâ€™s citizens. The art and culture programs often contain popular Javanese dance and music performances. Grabag TV also organised live coverage of elections for the village head, thus providing a new mechanism for monitoring local political processesâ€. Keywords: television, community, media literacy.